Development of quality control and structure parameters determination methods for large size products from sintered hard alloys WC-(Co+Ni+Cr) based on analysis of the ultrasonic oscillations spreading parameters - Pashynskyi, Volodymyr; Boyko, Igor (Technology audit and production reserves, 2021)
The object of research is hard alloys with a morphology of the carbide phase skeleton structure, in which particles contact with each other, and the gaps between them are filled with a binder phase. The mechanical and service characteristics of such materials depend on the degree of development of the skeleton structure. One of the most problematic areas is the lack of non-destructive methods for determining the parameters of the structure. The introduction of such techniques will allow obtaining objective information on the structure of the material and using it to evaluate the quality of products. In the course of the study, the parameters of the scattering of elastic vibrations in inhomogeneous media were determined. The main hypothesis of the study is the assumption that the processes of energy dissipation occur both in the structural elements themselves (carbide grains and bond areas) and at their boundaries. Therefore, the evaluation of dissipation processes will allow obtaining a quantitative estimation of the alloys structure parameters, and will allow assessing the quality of the material. The following characteristics were chosen as the parameters characterizing the propagation of ultrasonic oscillations: the speed of the oscillations propagation, the scattering background level in relation to the amplitude of the bottom reflection, the oscillations attenuation coefficient. The parameters were determined and compared with the characteristics of the quality of the products and the parameters of the microstructure, which were determined by the methods of quantitative metallography and the statistical characteristics of the relationship between the parameters, were determined. As a result, new quality control procedures for carbide products have been developed. The contiguity characteristics of the carbide skeleton of the sintered cemented carbide were determined by measuring the propagation speed of ultrasonic oscillations. The assessment of the level of porosity with a pore size of less than 1 mm was carried out according to the results of measuring the relative amplitude of the background scattering of ultrasonic oscillations. The proposed methods are non-destructive and are carried out in one cycle with ultrasonic flaw detection, to which 100% of the products are subjected. These techniques have been introduced in the production of carbide rolls by the method of controlled hot vacuum pressing. They have become an integral part of the quality control system for carbide rolls.